Intercultural competences and social media: contribution through research - Jakubowski, Jakub (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
Intercultural research in the area of communication was initiated in the early 20th century. Over the last few decades, researchers have built a solid theoretical basis in this field. Nowadays, intercultural analyses include a rich collection of texts on cross-cultural differences, the specificity of the phenomenon in the area of verbal and non-verbal communication and also the role of the media. There is no doubt that in an era of dynamic transformations of media use by people all over the world, the sub-discipline of intercultural communication is facing another challenge – that of including social media and network communication processes into new empirical theories and research. The article answers the question of the status of communication research in the field of the intercultural contexts of the new media. Additionally, the directions of future development of these studies and conclusions are discussed.